2018
DOI: 10.1093/jhps/hny028
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic labral reconstruction using fascia lata allograft: shuttle technique and minimum two-year results

Abstract: The purpose of this study was to describe the shuttle technique of acetabular labral reconstruction using allograft fascia lata and report minimum two-year clinical outcomes in a prospective patient cohort. We present a shuttle technique to introduce and fixate the allograft, by which the need to fix the free end of the graft from inside the joint is avoided. Between October 2010 and March 2014, 693 hip arthroscopic surgeries were performed by the senior author. Of these 693 patients, 34 patients underwent a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Mazek 24 Carreira et al 3 Rathi overall changes in patient-reported outcomes between autograft and allograft, qualitatively the data appear very similar. Overall, we were able to analyze the change in mHHS for a combined 6 studies (4 autograft, 2 allograft) and found that the pre-to postoperative improvement was statistically significant.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Mazek 24 Carreira et al 3 Rathi overall changes in patient-reported outcomes between autograft and allograft, qualitatively the data appear very similar. Overall, we were able to analyze the change in mHHS for a combined 6 studies (4 autograft, 2 allograft) and found that the pre-to postoperative improvement was statistically significant.…”
Section: Discussionmentioning
confidence: 75%
“…The postoperative mHHS for each study is shown in Figure 2. Additionally, 6 studies (2 allograft 3,25 and 4 autograft 1,7,14,24 ) provided sufficient data to conduct a meta-analysis comparing pre- versus postoperative mHHS scores (Figure 3). The random effects pooled mean difference in the mHHS, based on these 6 studies and a total of 315 patients, was an improvement of 29.0 points (95% CI, 20.2-37.8; P < .0001).…”
Section: Resultsmentioning
confidence: 99%
“…This technique offers a more precise and efficient way to measure labral defect size by using principles of graft measurement used in superior capsular reconstruction in the shoulder. Arthroscopic acetabular labral reconstruction using a shuttle technique appears to be an effective procedure for the treatment of labral pathology through minimum 2-year follow-up 1 . Although not previously reported as a potential complication in femoroacetabular impingement surgery, overresection is a concern.…”
Section: Discussionmentioning
confidence: 95%
“…Then, the allograft is shuttled into the joint through the DALA portal with an arthroscopic knot pusher. The limb from the midanterior portal is pulled and fully seated into the anteromedial anchor first, followed by the limb exiting the DALA portal (Carreira's Shuttle technique) 1 and secured to the acetabulum with a standard arthroscopy half-hitch knot-tying technique. This step is then repeated using one of the suture arms from the posterolateral end of the graft.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The number of arthroscopic hip surgeries for acetabular labral tears and femoroacetabular impingement (FAI) has been increasing worldwide [ 4–6 ]. PROMs, such as the Non-Arthritis Hip Score [ 7 ] and the Hip Outcome Scores [ 8 ], have been accepted as useful clinical measures [ 9–11 ]. However, these PROMs were developed in English-speaking regions only; therefore, direct application of PROMs in the English language in patients who do not speak English as their first language may not be optimal because of the potential misunderstanding and lack of comprehension regarding the content of the inquiries.…”
Section: Introductionmentioning
confidence: 99%